IN SILICO STUDY OF ELASTASE ENZYME WITH NAPHTHOQUINONE DERIVATIVES AS LIGAND - Farhan, Muhammad Rafiq; Alwi, Ratna Surya; Harahap, Mahyuni; Purwandari, Vivi (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2023)
We simulated 17 molecules classified as Naphthoquinones derivatives with the Enzyme Elastase to observe data regarding energies produced after bonding. These 17 Molecules were Eleutherin, Isoeleutherin, Elacanacin, Eleutherinone, Eleutherol A, Eleutherol B, Eleutherol C, Eleuthinones B, Eleuthinones C, Eleutherine A, Eleutherine B, Eleutherine C, Eleutherine D, Eleutherine E, Eleutherine F, Eleutherine G, Eleucanainones A. To prepare the ligand and protein for docking, we used the Discovery Studio application. For the molecular docking itself, we used the Pyrx application. Regarding interpreting the result, first, we chose the lowest rmsd/ub or rmsd/lb, and then we analyzed the energy result in which the lowest rmsd occurred. The docking results data indicated that all the ligand-enzyme bonding had negative binding affinity energy, but Eleucanainones A produced the lowest energy (Binding Affinity -7.7, mode 1, Rmsd/ub 1.787, Rmsd/lb 3.54), meaning it bound most easily with the enzyme Elastase. This study was only an initial or foundational step and further studies were highly needed for the development of the correlation between the ligands and the enzyme mentioned above.